Management of Hemodynamically Unstable Pelvic Ring Fractures - Benders, Kim E. M.; Leenen, Luke P. H. (Frontiers in Surgery, 2020)
Hemodynamically unstable pelvic fractures are challenging high-energy traumas. In many cases, these severely injured patients have additional traumatic injuries that also require a trauma surgeon’s attention. However, these patients are often in extremis and require a multidisciplinary approach that needs to be set up in minutes. This calls for an evidence-based treatment algorithm. We think that the treatment of hemodynamically unstable pelvic fractures should primarily involve thorough resuscitation, mechanical stabilization, and preperitoneal pelvic packing. Angioembolization should be considered in patients that remain hemodynamically unstable. However, it should be used as an adjunct, rather than a primary means to achieve hemodynamic stability as most of the exsanguinating bleeding sources in pelvic trauma are of venous origin. Time is of the essence in these patients and should therefore be used appropriately. Hence, the hemodynamic status and physiology should be the driving force behind each decision-making step within the algorithm.